2023
DOI: 10.3233/wor-211161
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID-19 pandemic on weight gain, physical activity and mental health among Turkish university students

Abstract: BACKGROUND: The COVID-19 pandemic has brought many restrictions that affected Turkey as well as other countries around the world. Restrictions on education, sports activities and social activities affected students physically and psychologically. OBJECTIVE: The aim of this study is to investigate the impact of the COVID-19 pandemic on weight gain, physical activity, and mental health among university students. METHODS: The study included students of Pamukkale University aged between 18–25 years. Participants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Frontiers in Neuroscience 11 frontiersin.org negative impact on their mental health (Soysal et al, 2023). The third topical area in this field is negative behaviors that affect the mental health of college students, such as risk factors, sedentary behavior, prevalence, sleep, and psychological (blue cluster).…”
Section: Analysis Of Co-occurring Abstract and Visualization Based On...mentioning
confidence: 99%
“…Frontiers in Neuroscience 11 frontiersin.org negative impact on their mental health (Soysal et al, 2023). The third topical area in this field is negative behaviors that affect the mental health of college students, such as risk factors, sedentary behavior, prevalence, sleep, and psychological (blue cluster).…”
Section: Analysis Of Co-occurring Abstract and Visualization Based On...mentioning
confidence: 99%
“…Among these changes, the lack of physical activity and bad eating habits had an important impact on the population's health, such as overweight and obesity. (King et al, 2020; Navarro‐Cruz, et al, 2021; Santana et al, 2021; Soysal et al, 2023). In this sense, two independent studies reported that harmful changes in eating habits during the pandemic led to weight gain among university students in Chile (Navarro‐Cruz et al, 2021) and Turkey (Soysal et al, 2023) and was related to an increase in depressive symptoms (Soysal et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…(King et al, 2020; Navarro‐Cruz, et al, 2021; Santana et al, 2021; Soysal et al, 2023). In this sense, two independent studies reported that harmful changes in eating habits during the pandemic led to weight gain among university students in Chile (Navarro‐Cruz et al, 2021) and Turkey (Soysal et al, 2023) and was related to an increase in depressive symptoms (Soysal et al, 2023). Furthermore, habit changes due to social isolation may be related to the appearance of new pathologies and clinical worsening of diseases such as dyslipidemia, insulin resistance, hypertension, and visceral obesity (King et al, 2020).…”
Section: Introductionmentioning
confidence: 99%